2023
DOI: 10.3390/cells12121668
|View full text |Cite|
|
Sign up to set email alerts
|

Starvation Protects Hepatocytes from Inflammatory Damage through Paradoxical mTORC1 Signaling

Abstract: Background and aims: Sepsis-related liver failure is associated with a particularly unfavorable clinical outcome. Calorie restriction is a well-established factor that can increase tissue resilience, protect against liver failure and improve outcome in preclinical models of bacterial sepsis. However, the underlying molecular basis is difficult to investigate in animal studies and remains largely unknown. Methods: We have used an immortalized hepatocyte line as a model of the liver parenchyma to uncover the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…However, increasing numbers of studies have demonstrated that the body’s energy status contributes to postpartum endometritis infection. With in-depth investigation, the correlation between inflammation and energy has been further clarified ( Hussain et al, 2023 ). According to the present study, treatment of BEEC with LPS causes energy loss as evidenced by decreased ATP levels, and this energy loss is intensified by culture in low glucose media, which replicates the state of NEB during endometritis.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing numbers of studies have demonstrated that the body’s energy status contributes to postpartum endometritis infection. With in-depth investigation, the correlation between inflammation and energy has been further clarified ( Hussain et al, 2023 ). According to the present study, treatment of BEEC with LPS causes energy loss as evidenced by decreased ATP levels, and this energy loss is intensified by culture in low glucose media, which replicates the state of NEB during endometritis.…”
Section: Discussionmentioning
confidence: 99%